EFEKTIFITAS MEDIATOR DALAM MELAKUKAN MEDIASI PADA PERKARA KEWARISAN DI PENGADILAN AGAMA WATAMPONE KELAS 1 A - Samsidar; Hanuddin, La (Institut Agama Islam Negeri Bone, 2023)
This study explores the effectiveness of mediators in mediating inheritance cases at the Watampone Class 1A Religious Court. Mediation is an alternative dispute resolution that aims to reach a peaceful agreement between the disputing parties. The method used in this study is qualitative with a normative juridical approach, where data is collected through in-depth interviews, direct observation, and document analysis. The results of the study show that mediators use various communication techniques to create a conducive atmosphere and reduce tension between parties. In addition, mediators also play a role in providing relevant legal information and helping parties understand their rights and obligations. The effectiveness of the mediation process carried out by mediators in inheritance cases at the Watampone Class 1A Religious Court can be seen from the level of success in reaching an agreement between the parties involved in the mediation. If the mediation succeeds in reaching an agreement that is acceptable to all parties, then the mediation process is considered effective. In addition, the court can also assess the effectiveness of mediation through the satisfaction of the parties with the results achieved. The implications of this research provide a significant contribution to understanding the mediation process in resolving inheritance cases and can serve as a reference for courts and mediators in improving the effectiveness and quality of future mediations. Thus, mediation is expected to be a more effective and efficient alternative dispute resolution process compared to litigation.